NILAI-NILAI KEASWAJAAN DALAM KRITIK KH. M. HASYIM ASY’ARI TERHADAP PEMIKIRAN WAHABI - Muhammad Abror Rosyidin (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2021)
Abstract KH. M. Hasyim Asy'ari was the central figure of the Indonesian Muslims in the 19th century. His fatwa and criticism of a particular phenomenon attracted the attention of the Islamic world from various circles, not only in Indonesia but also internationally. Including his response to the emergence of new sects in Islam that claim to be a reformer movement. Researchers are interested in examining Ahlussunnah wal Jama’ah (Aswaja) values in various criticisms of Kiai Hasyim against the movement, in his various literatures. There are three (3) focuses in this research, namely: (1) The emergence of Wahhabis and its development in Indonesia, (2) Aswaja values in critiques of KH. M. Hasyim Asy'ari against Wahhabism, and (3) Socio-Historical-Political Analysis of KH. M. Hasyim Asy'ari to the Wahhabism. This study uses a qualitative approach to literature study with analytical descriptive data analysis. The research design used is to do a literature study that is in accordance with the discussion and conduct interviews that are needed to complete the data with several informants. The next step is to reduce the data obtained, analyze, and obtain conclusions according to the research focus. The results of this study indicate Aswaja values according to KH. M. Hasyim Asy'ari from Wahhabism that need to be clarified, namely: (1) the meaning of the term